Photocatalytic Activity of Cr(VI) and Mn(VII) Loaded CaCO3 under Sunlight Radiation - Kaur, Davinder (My University, 2019)
This study demonstrated the extraction of CaCO3 from boiling tap water followed by its calcination at 900°C. Two metals ions with different oxidation states (Cr+6, Mn+7; 1wt%) were deposited over the surface of CaCO3 (RT, 900°C) to study the adsorption and photo catalytic degradation of RB dye. Different techniques like DLS, XRD, DRS, SEM and UV-Vis spectrophotometer were used to characterize as-prepared photocatalysts. The DRS spectra revealed that CaCO3 (900°C) shows absorption spectra at 245 nm which was red shifted to 364 nm and 531 nm after deposition of Cr+6 and Mn+7 respectively. The average hydrodynamic size of bare CaCO3 (900°C) is 0.63 μm which is increased to 1.34 μm for Cr+6-CaCO3 (900°C)and 1.48 μm for Mn+7-CaCO3 (900°C) after metal ion impregnation. The hierarchical morphology was observed and the EDX-mapping studies revealed the presence of Cr+6 and Mn+7 ions doped on CaCO3. The crystalline size of Cr+6-CaCO3 (900°C) (101 Å) and Mn+7-CaCO3 (900°C) (127 Å) was calculated using FWHM. The adsorption behaviour of RB dye follows Freundlich adsorption isotherm with R2 = 0.99 and n=0.47. It was found out that Mn+7-CaCO3(900°C) showed enhanced degradation efficiency (92%) compared to CaCO3(900°C) (73%) with higher rate constant (k) value of 4.6×10-2 min-1 .
Keywords: Calcium Carbonate; Photcatalytic Acitvity; Sunlight